Effect of dietary tall oil fatty acids and hydrolysed yeast in SNP2-positive and SNP2-negative piglets challenged with F4 enterotoxigenic Escherichia coli - Anouschka Middelkoop; Hannele Kettunen; Xiaonan Guan; Juhani Vuorenmaa; Ramon Tichelaar; Michela Gambino; Martin Peter Rydal; Francesc Molist (Scientific Reports)
Abstract Reduction of post-weaning diarrhoea caused by ETEC is a principal objective in pig farming in terms of welfare benefits. This study determined the effects of genetic susceptibility and dietary strategies targeting inflammation and fimbriae adherence on F4-ETEC shedding and diarrhoea in weaned piglets in an experimental challenge model. A DNA marker test targeting single nucleotide polymorphism 2 (SNP2) identified piglets as heterozygous (SNP2+, susceptible) or homozygous (SNP2-, resistant) to developing F4ac-ETEC diarrhoea. A total of 50 piglets, 25 SNP2+ and 25 SNP2-, were weaned at 30 days of age and equally distributed to different treatments (n = 10): Positive control (PC): piglets fed with a negative control diet and provided with colistin via drinking water; Negative control (NC): piglets fed with a negative control diet; Tall oil fatty acids (TOFA): piglets fed with a negative control diet + 1.0 g TOFA/kg feed; Yeast hydrolysate (YH): piglets fed with a negative control diet + 1.5 g YH/kg feed derived from Saccharomyces cerevisiae; and Combination (COM): piglets fed with a negative control diet + 1.0 g TOFA and 1.5 g YH/kg feed. On day 10 post-weaning, all piglets were infected with F4-ETEC by oral administration. Piglets fed with PC, TOFA, YH or COM had a lower faecal shedding of F4-ETEC than NC piglets (P < 0.001), which was also shorter in duration for PC and TOFA piglets than for NC piglets (P < 0.001). Piglets in PC, TOFA, YH and COM had a shorter diarrhoea duration versus NC when classified as SNP2+ (P = 0.02). Furthermore, PC, TOFA and YH piglets grew more than NC and COM piglets in the initial post-inoculation period (P < 0.001). In addition, the level of faecal F4-ETEC shedding and the percentage of pigs that developed F4-ETEC diarrhoea (72 vs. 32%, P < 0.01) following infection were higher, and the duration of F4-ETEC diarrhoea longer (2.6 vs. 0.6 days, P < 0.001), in SNP2+ piglets than in SNP2- piglets, and led to reduced growth performance (P = 0.03). In conclusion, piglets fed with TOFA, YH or their combination, irrespective of their SNP2 status, are more resilient to F4-ETEC infection. Moreover, SNP2+ piglets show a higher level of F4-ETEC shedding and diarrhoea prevalence than SNP2- piglets, confirming an association between SNP2 and F4ac-ETEC susceptibility.